Respiratory Failure in Acute Decompensated Heart Failure: A Case Report - Nuri Nurhasanah S; Theresia Monica Rahardjo; Gabriel Tangdirerung R; Angelina Simbolon; Andieni Faqhira P; Cyntia Carrisa; I. Gusti A.P; Fauziah Luthfianti; Revalitha Putri; Assyifa Putri U.; Muliani Ester R. (Medical Clinical Update, 2023)
Chronic respiratory failure is an acute respiratory failure that develop slowly. The symptoms are shortness of breath, extreme tiredness, an inability to exercise, and sleepiness. One of the causes of respiratory failure is acute decompensated heart failure (ADHF). ADHF It can be defined suddenly heart failure requiring hospitalization. ADHF is caused by acute coronary syndromes, COPD exacerbation, asthma, surgery, and drugs. If not treated properly, it can lead to stroke, liver congestion, atrial fibrillation, arrhythmia ventricular, and venous thrombosis